2020
DOI: 10.1085/jgp.202012716
|View full text |Cite
|
Sign up to set email alerts
|

Resting and stimulated mouse rod photoreceptors show distinct patterns of vesicle release at ribbon synapses

Abstract: The vertebrate visual system can detect and transmit signals from single photons. To understand how single-photon responses are transmitted, we characterized voltage-dependent properties of glutamate release in mouse rods. We measured presynaptic glutamate transporter anion current and found that rates of synaptic vesicle release increased with voltage-dependent Ca2+ current. Ca2+ influx and release rate also rose with temperature, attaining a rate of ∼11 vesicles/s/ribbon at −40 mV (35°C). By contrast, sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 94 publications
(129 reference statements)
7
25
0
Order By: Relevance
“…1) (Grassmeyer et al, 2019). As described earlier (Hays et al, 2020b), these inward currents had waveforms typical of quantal post-synaptic currents but with a slow time course (10-90% rise time of 9-10 ms with decay time constants of ∼40 ms). Spontaneous inward currents in rods voltage-clamped at -70 mV showed a unimodal amplitude distribution suggesting they consisted entirely of uniquantal events (Fig.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…1) (Grassmeyer et al, 2019). As described earlier (Hays et al, 2020b), these inward currents had waveforms typical of quantal post-synaptic currents but with a slow time course (10-90% rise time of 9-10 ms with decay time constants of ∼40 ms). Spontaneous inward currents in rods voltage-clamped at -70 mV showed a unimodal amplitude distribution suggesting they consisted entirely of uniquantal events (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Thus, dark adaptation might influence the statistics of vesicle release. However, when holding dark-adapted rods at -40 mV, we found that the number of vesicles in each multivesicular release event (16.7 ± 5.8, n=7) and the intervals between multivesicular event start times (2.0 ± 0.54 s, n=6, room temperature) did not differ significantly from those measured in light-adapted retinas (17 ± 7 v/burst, n=22, p=0.74, unpaired t-test; 2.4 ± 0.62 s intervals, n=14, p=0.18, unpaired t-test) (Hays et al, 2020b). Thus, recording from rods in light-adapted versus dark-adapted states did not strongly alter release statistics.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations